A Collectively Fixed Point Theorem in Abstract Convex Spaces and Its Applications. (14th July 2013) - Lu, Haishu; Hu, Qingwen
Abstract : The main purpose of this paper is to establish a new collectively fixed point theorem in noncompact abstract convex spaces. As applications of this theorem, we obtain some new existence theorems of equilibria for generalized abstract economies in noncompact abstract convex spaces.